Pemasangan Lampu Sistem Otomatis Berbasis Photocell dan Sensor Gerak di Jembatan Dermaga Nelayan RT 26 Kelurahan Manggar Baru - Rinto Rinto; Maha Setya Adi Putra; Auliza Alifin Nadhiro; Afifah Nabila Ramadhani; Arif Ramadhan; Khairul Umam; Andra Irwanto; Dityo Cahyo Anggoro; Jumsari Jumsari; Diva Raissa Nabilah; Dimas Wahyu Wibowo (Abdimas Universal, 2024)
Lighting lamps are usually operated manually by humans. With current technological advances, human intervention in operations is being reduced. An automatic switch will make operations easier, effective and efficient to avoid lights burning in vain without any activity. The aim is none other than to avoid wasting electrical energy. This dedication takes the topic of designing a bridge lighting installation for a group of fishermen. This automatic switch uses input in the form of a Passive Infrared (PIR) human presence sensor and a light dependent resistor (LDR/Photocell) type light intensity sensor. PIR is a pyroelectric sensor which has a momentary response to the movement of objects and heat energy in living things. The heat source is radiated with infrared. The human body produces heat energy which is radiated by infrared. The human body's heat radiation will be received by the sensor for the circuit input response. The complete circuit consists of a passive infrared sensor, fresnel lens, main circuit, power supply, LDR and lighting load. In essence, the PIR and LDR will be transistor drivers. The transistor functions as an electronic switch that will disconnect and connect the lighting load. Light installation is carried out in the RT area. 26 Manggar Baru Subdistrict. Installing these lights is very beneficial for local residents, especially for fishermen when they want to dock their boats after fishing.